UPAYA MENINGKATKAN PERENCANAAN KARIR SISWA MELALUI BIMBINGAN KELOMPOK TEKNIK MIND MAPPIING PADA KELAS X DI SMA NEGERI 10 PALEMBANG - Citra Annisa (Kopertis Region IV Jabar and Banten, 2025)
This Classroom Action Research in the field of Guidance and Counseling (CAR-GC) aims to determine the effectiveness of using self-management techniques to improve advanced study planning skills among Grade X.3 students of SMA Negeri 10 Palembang through group counseling services. The research involved seven students (MFA, BNI, MPAR, KPS, ASP, MBA, MS) as subjects and was conducted over three cycles, each consisting of planning, implementation, evaluation, and reflection stages. Data were collected using participatory observation and semi-structured interviews. The findings of this study indicate that selfmanagement techniques are proven effective in enhancing students' ability to plan for further studies. (Detailed results of each cycle will be presented in the results and discussion section). This research is expected to make a positive contribution to guidance and counseling practitioners in improving their ability to support students in planning their future education.